Lactic Acid Fermentation Exposed to Some Alkaloids - Chauhan, R.P.S.; Dubey, V.K.; Bahadur Singh, Uttam (Asian Journal of Chemistry, 2010)
A quick and convenient method has been developed for the microdetermination of few hydrazine derivatives. Milligram amount of the sample is allowed to react with excess of N-chlorosaccharin at room temperature for 10 minutes. After the reaction is over, the unconsumed reagent is back titrated iodometrically. The accuracy of the method is within ±0.5%